A new family of silver(i) complexes stabilised by the phosphanylborane (C6H5)2PBH2·N(CH3)3. (31st July 2020) - Elsayed Moussa, Mehdi; Marquardt, Christian; Hegen, Oliver; Seidl, Michael; Scheer, Manfred
Abstract : By the reaction of the phosphanylborane Ph2 PBH2 ·NMe3 with Ag[FAl{OC6 F10 (C6 F5 )}3 ] or Ag[BF4 ] first Ag(i ) coordination compounds stabilized by phosphine-boranes were obtained. Abstract : The reactions of the phosphanylborane Ph2 PBH2 ·NMe3 (L ) with Ag[FAl{OC6 F10 (C6 F5 )}3 ] (Ag[FAl]) and AgBF4 are studied. The first reaction allowed for the synthesis of the coordination compounds [Ag(Ph2 P-BH2 ·NMe3 )(CH3 CN)][FAl] (1 ), [Ag(Ph2 P-BH2 ·NMe3 )2 ][FAl] (2 ) and [Ag(Ph2 P-BH2 ·NMe3 )3 ][FAl] (3 ), while the second reaction afforded the one-dimensional coordination polymer [Ag(Ph2 P-BH2 ·NMe3 )] n [BF4 ] n (4 ). Compounds 1–4 are the first reported Ag(i ) complexes stabilised by phosphanylboranes.